May Measurement Month 2019: an analysis of blood pressure screening results from the United Kingdom and Republic of Ireland. (20th May 2021) - McDonnell, Barry J; Rees, Emma; Cockcroft, John R; Beaney, Thomas; Clayton, Bethan; Le Kieu, Phuong; Brady, Adrian J B; Padmanabhan, Sandosh; McCallum, Linsay; Dolan, Eamon; O'Brien, Eoin; Tomaszewski, Maciej; et al.
Abstract: In the UK, heart and circulatory diseases account for 29% of all deaths (14% through coronary heart disease and 8% through stroke). In 2015, the prevalence of hypertension was 20% in the UK and 23% in the Republic of Ireland. In 2019, 14% of people registered with a UK general practice had hypertension and yet it was the attributable risk factor for around half of all deaths from coronary heart disease or stroke. We participated in May Measurement Month 2019 to increase awareness of blood pressure (BP) measurement, and to identify the proportion of undiagnosed hypertension and degree of uncontrolled hypertension in the community. The 2019 campaign set up screening sites within the community at places of worship, supermarkets, GP surgeries, workplaces, charity events, community pharmacies, gyms, and various other public places. We screened 10194 participants (mean age 51 ± 18 years, 60% women) and found that 1013 (9.9%) were on antihypertensive treatment, while 3408 (33.4%) had hypertension. Of the 3408 participants with hypertension, only 33.5% were aware of their condition despite 98.8% having previous BP measurements. In those on antihypertensive medication, only 38.2% had controlled BP (<140 and <90 mmHg). Our UK and Republic of Ireland data demonstrate concerning levels of undiagnosed hypertension and sub-optimal BP control in many individuals with a diagnosis. This evidence supports a critical need for better systematic community and primary care screening initiatives.